(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
The proliferation of privately owned institutions in Nigeria has led to a range of challenges, including the issue of workplace diversity. The observed phenomenon is a naturally occurring event that can have varying effects on worker performance, depending on the effectiveness of its management. Numerous research studies have demonstrated the significant impact of non-teaching personnel management on their performance in private university settings. This study investigates the influence of workplace diversity on the efficacy of human resource management, expanding on the existing theoretical framework. The study utilised a survey research method, specifically targeting private universities in Ogun State that have obtained approval from the National Universities Commission (NUC). A representative sample of respondents was selected. The data was collected using a meticulously designed questionnaire. Regression analysis of ordinary least squares (OLS) and Pearson product correlation were used to analyse workplace diversity and human resources performance among non-teaching staff in a selected private university in Nigeria. The regression analysis conducted in this study revealed a statistically significant association between workplace diversity, encompassing factors such as age, education, and gender, and employees’ performance in Nigeria. Ethnic diversity has a detrimental effect on workplace diversity. The study indicates that it is important for organisational management to establish and implement policies that support diversity in the workforce, considering the varied backgrounds of all individuals involved.